Let $f,g:[0,1] \to \mathbb{R}$ such that $f'(x)>0,\ g'(x) >0,\ \forall x\in [0,1]$. Moreover, $f(0)= g(0)$ and $f(1)=g(1)$. Prove that exists $x_1, x_2 \in [0,1]$ such that $$f(x_1) = g(x_2), \ \text{and}\ \ f'(x_1) = g'(x_2)$$

I've tried to use Mean Value Theorem with:

a) $h(x)= f(x)-g(x)$

b) $h(x) = f(x) - xg(x)$

c) $h(x) = f(x)g(x)$

d) Using $g(1-x)$ instead of $g(x)$

But nothing seems to help in order to find at least one of $x_1$ or $x_2$. I think that, finding one of them, the other could be easy to get.

Thanks for the help!


2 Answers 2


Strategy: there are lots of pairs $x_1,x_2$ such that $f(x_1)=g(x_2)$: just take any $y\in[0,1]$ and force $f(x_1)=y$ and $g(x_2)=y$ — in other words, set $x_1=f^{-1}(y)$ and $x_2=g^{-1}(y)$. So let's use that parametrization to study the other desired equality $f'(x_1)=g'(x_2)$.

Proof: Note that $f(f^{-1}(y)) = y = g(g^{-1}(y))$ for all $y\in[0,1]$. By the chain rule, $$ f'(f^{-1}(y)) \frac d{dy}f^{-1}(y) = g'(g^{-1}(y)) \frac d{dy}g^{-1}(y) \tag{1} $$ for all $y$.

Set $a=f(0)=g(0)$ and $b=f(1)=g(1)$. Note that $f^{-1}(a) = 0 = g^{-1}(a)$ and $f^{-1}(b) = 1 = g^{-1}(b)$. Hence, by the mean value theorem (indeed, Rolle's theorem) applied to $f^{-1}-g^{-1}$ on the interval $[a,b]$, there exists $y_0\in(a,b)$ such that $\frac d{dy}f^{-1}(y_0) = \frac d{dy}g^{-1}(y_0)$.

Therefore, by (1), $f'(f^{-1}(y_0)) = g'(g^{-1}(y_0))$. Now set $x_1 = f^{-1}(y_0)$ and $x_2 = g^{-1}(y_0)$.

  • $\begingroup$ Everything is so clear, except for $f^{-1}(0)=(0)$. I don't see that $\endgroup$
    – FormerMath
    Oct 12, 2014 at 17:51
  • $\begingroup$ Woops, I misread that part of the problem. Edited to fix. $\endgroup$ Oct 12, 2014 at 21:55

I suggest that you look at $h(x) = g^{-1}(f(x))$. Suppose that for some number $x_1$, $h'(x_1) = 1$. What would that tell you?

Also: How do you know $g^{-1}$ even exists? You need to answer this before you go using it willy-nilly.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.